Receptor interacting protein kinase 1 mediates murine acetaminophen toxicity independent of the necrosome and not through necroptosis. Issue 6 (31st July 2015) - Dara, Lily; Johnson, Heather; Suda, Jo; Win, Sanda; Gaarde, William; Han, Derick; Kaplowitz, Neil
Abstract : Although necrosis in the acetaminophen (APAP) model is known to be regulated by c‐Jun NH2‐terminal kinase (JNK) through interaction with mitochondria, the role of necroptosis through receptor‐interacting proteins 1 and 3 (RIPK1 and RIPK3) has also been suggested. Our aim was to determine the relationship between these two mechanisms of cell death. To verify the participation of RIPK1, we used antisense knockdown and confirmed protection comparable to the RIPK1 inhibitor, necrostatin, in vivo and in vitro . However, we found no evidence that RIPK3 is expressed in primary mouse hepatocytes under basal conditions or after APAP and RIPK3 −/− mice were not protected. RIPK3 was exclusively expressed in nonparenchymal cells. RIPK1 knockdown protected RIPK3 −/− mice to the same extent as wild‐type mice, underscoring the independent role of RIPK1. We confirmed that necroptosis is not involved in APAP toxicity by using mixed lineage kinase domain‐like protein (MLKL) knockout mice, which were not protected from APAP. Next, we addressed whether there is interplay between RIPK1 and JNK. RIPK1 knockdown decreased the level of JNK activation and translocation to mitochondria and abrogated subsequent translocation of dynamin‐related protein 1 (Drp1). Interestingly, APAP induced translocation of RIPK1 to mitochondria, which was unaffected by knockdown of the mitochondrial JNK docking protein, Sh3 homology 3 binding protein 5 (Sab). Conclusion : RIPK1 participates in APAP‐induced necrosis upstream of JNK activation whereas RIPK3 and MLKL are dispensable, indicating that necroptosis does not contribute to APAP‐induced necrosis and RIPK1 has a unique, independent role.(Hepatology 2015;62:1847–1857)